AN INVESTIGATION ON GENDER DISPARITIES OF CHURCH MEMBERSHIP AND ATTENDANCE: A CASE OF MBOONI WEST SUB-COUNTY IN MAKUENI COUNTY, KENYA - Racheal Syombua Muli,; Prof. Paul Kyalo,; Dr. Regina W. Kinuthia, (IJRDO - Journal of Social Science and Humanities Research, 2020)
Gender disparities are prevalent in most churches around the globe. Ideally, the number of men who attend churches is significantly lower than that of women. Numerous past studies have affirmed this assertion by postulating evidence-based arguments that show that there are more women than men in the church. Gender imbalance in churches has proved to be a social problem that needs to be addressed in order to change the status quo. Remarkably, it is imperative to first examine the underlying factors that contribute to this imbalance. This study was conducted to investigate the prevalence of gender disparities in church attendance and membership in Mbooni West sub county churches. Primarily, the study was aimed at answering the following questions: What is the ratio of men to women in church membership and attendance? Which factors influence church membership and attendance? What is the theological foundation behind church membership and attendance? What is the role of the church leadership in mainstreaming church membership and attendance among men? The research design used in this study is majorly based on a quantitative approach as it relies much on numerical figures and statistics. For instance, the researcher selected a total of fifteen (15) churches out of the one hundred and fifty-six (156) churches that are located in Mbooni West Sub County. The sub county has three divisions namely Mbooni, Kalawani and Tulimani. Purposive sampling was used to select five main churches that were to be studied. These comprised of the African Inland Church(A.I.C),the Roman Catholic church(R.C),the Africa Brotherhood Church(A.B.C),the seventh Day Adventist Church(SDA) and the Salvation Army(S.A).One branch of each of the churches was identified through random sampling. Primarily, the researcher conducted interviews with relevant priests/pastors. Further, two women and two men are church goers were selected through subjective sampling in each of the fifteen churches. Open questionnaires were administered to the selected cohorts. Additionally, the researcher interviewed 30 men who are not church goers. The study findings indicated that there are fewer men than women in Mbooni West Sub county churches. Besides, it was established that cultural, economic, religious and natural attributes are some of the factors that contribute to the disparities. Consequently, the researcher recommended that creation of awareness and sensitization on the importance of church membership among men was necessary. Holding of seminars and workshops to remediate the disparities one of the strategies recommended in this study. Additionally, other scholars are called upon to examine the same subject matter and come up with alternative recommendations